Status Gizi dan Aktivitas Fisik dengan Gangguan Lambung pada Mahasiswa - Yuni Sara Yuni Sara; Izna Nurdianty Muhdar; Rahmatika Nur Aini (Sarana Ilmu Indonesia (salnesia), 2021)
Gastric disorders are diseases that interfere with activities and if not treated properly can be fatal. One of the gastricdisorders is dyspepsia syndrome, a medical condition characterized by pain or discomfort in the upper abdomen or solarplexus. Adolescents are a group at risk for dyspepsia syndromethis causes reduced time for physical activity, and does notpay attention to nutritional status.The purpose of this study for identify the relationship between nutritional status and level of physical activity with gastric disorders in collage students.This research use a study design with (cross sectional) study design.Determination of the sample using the Proportional Stratified Random Sampling technique with the numberof respondents 85 subject collecting data using the Rome III questionnaire and the PAR (Physical Activity Ratio).The result of the study, it was found that there was a significant relationship between nutritional status and gastric disorders with a p-value of 0,0167 (P<0,05) with PR (Prevalens Ratio)=5,797.While the level of physical activity was not related with gastric disorders with a value of p = 0.2 (p> 0.05).